Keanekaragaman Jenis Lumut (Musci) di Lereng Gunung Wani, Suaka Margasatwa Buton Utara, Sulawesi Tenggara - Florentina Indah Windadri (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2008)
Diversity study on mosses at the slope of Wani mountain, North Buton Wild Life Reserve, South-east Sulawesi was conducted. There are 26 species belong to 14 genera and 8 families are recorded. Two genera i.e. Thuidium and Himanthocladium dominated in this area. Sixth species are recorded as “new record” to Sulawesi i.e. Barbella pendula,Calyptotheciumcaudatum, Himantocladium plumula, Pinatella ambigua, Taxithelium alare, and Thuidium investe.